If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-64z=-15-4z
We move all terms to the left:
-64z-(-15-4z)=0
We add all the numbers together, and all the variables
-64z-(-4z-15)=0
We get rid of parentheses
-64z+4z+15=0
We add all the numbers together, and all the variables
-60z+15=0
We move all terms containing z to the left, all other terms to the right
-60z=-15
z=-15/-60
z=1/4
| -1+4x+12=0 | | 2(3x-10)=26 | | 13=8p-15-7p | | 10y+15=7y+3 | | 10y-15=7y+3 | | 10y+15=7y-3 | | 8m-7=3m+43 | | 8x=78−5x | | 5x+3=2x,-3 | | 1/2g=2/3 | | 25=d+6.2 | | a/2-5+8=14 | | m/4+6-2=7 | | 15y-6y=-2 | | 6(t-4)=26-8 | | 6x+14=7x-19 | | x+(x*0.08)=22 | | 9(12-a)=63 | | 7(m+9=112 | | x/9,4=10 | | w/12-3=6 | | 6x+4=7x-8 | | t/9+8=11 | | n/5-12=2 | | m/8-4=3 | | 5(a+)=3a+31 | | x²+8x-600=0 | | 4(n-8)=64 | | 20x+7=27 | | 8-9p-10=4p+23 | | 53a=55=42a | | (x-3)^2=18 |